Conditional Cash Transfers and Labour Informality: The Case of Argentina - Gasparini, Leonardo Carlos (2015)
The Universal Child Allowance for Social Protection (AUH) is Argentina’s main conditional cash transfer (CCT) programme, launched in 2009 by the federal government with ample social and political support. This is a key, massive initiative to broaden the coverage of the welfare state to the entire population and alleviate the typical imbalance of Latin American social protection systems, which are biased toward formal employees.